2012
DOI: 10.1152/ajpcell.00167.2011
|View full text |Cite
|
Sign up to set email alerts
|

Static mechanical stretching accelerates lipid production in 3T3-L1 adipocytes by activating the MEK signaling pathway

Abstract: Understanding mechanotransduction in adipocytes is important for research of obesity and related diseases. We cultured 3T3-L1 preadipocytes on elastic substrata and applied static tensile strains of 12% to the substrata while inducing differentiation. Using an image processing method, we monitored lipid production for a period of 3-4 wk. The ratio of %-lipid area per field of view (FOV) in the stretched over nonstretched cultures was significantly greater than unity (P < 0.05), reaching ∼1.8 on average startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 81 publications
(96 reference statements)
4
76
0
Order By: Relevance
“…As opposed to these studies, using a non-destructive imageprocessing-based method, we have recently reported that delivering static mechanical stretching by applying substrate tensile strain (STS) of 12% to 3T3-L1 preadipocytes during the timecourse of differentiation (for about 4 weeks), accelerates the lipid production. 28 We further found that the accelerated adipogenesis in the stretched cultures was associated with activation of the mitogen-activated protein kinase kinase (MEK) signaling pathway. 28 However, it remained unclear which specific levels of STS trigger the accelerated adipogenic response.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…As opposed to these studies, using a non-destructive imageprocessing-based method, we have recently reported that delivering static mechanical stretching by applying substrate tensile strain (STS) of 12% to 3T3-L1 preadipocytes during the timecourse of differentiation (for about 4 weeks), accelerates the lipid production. 28 We further found that the accelerated adipogenesis in the stretched cultures was associated with activation of the mitogen-activated protein kinase kinase (MEK) signaling pathway. 28 However, it remained unclear which specific levels of STS trigger the accelerated adipogenic response.…”
Section: Introductionmentioning
confidence: 90%
“…28 We further found that the accelerated adipogenesis in the stretched cultures was associated with activation of the mitogen-activated protein kinase kinase (MEK) signaling pathway. 28 However, it remained unclear which specific levels of STS trigger the accelerated adipogenic response.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations